Prediction and analysis of trends in the nutritional status of children under 5 years in Iran: reanalysis of the results of national surveys conducted between 1998 and 2020 - Ghodsi, Delaram; Rasekhi, Hamid; Yari, Zahra; Roustaee, Roshanak; Nikooyeh, Bahereh; Faramarzi, Ayoub; Eini-Zinab, Hassan; Neyestani, Tirang R. (Frontiers in Nutrition, 2023)
Abstract Background and aim. Malnutrition is one of the major public health problems, especially in developing countries. The aim of the present study was to analyze the trend of malnutrition in children under 5 years of age in Iran in the past decades and to estimate malnutrition status for 2020. Methods. This study is a secondary analysis of the reports and data of three cross-sectional national surveys on children nutritional status conducted between 1998 and 2017. Anthropometric indices indicating underweight, wasting, stunting, and overweight and obesity were used as indicators of nutritional status of children under 5 years. Malnutrition indicators were reported separately based on food security status. Linear mixed effect models analysis was used to predict the status of malnutrition indicators in 2020. Results. The results of the present study demonstrated a downward trend in the prevalence of stunting, underweight and wasting, from 15.4 to 4.8, 10.9 to 4.3 and 4.9 to 4.3 percent, respectively from 1998 to 2017. The prevalence of at risk of overweight and overweight children showed a downward trend between 2010 and 2018, from 3.73 to 3.02 and from 12.1 to 10.3 percent, respectively. However, the trend of changes was different in various provinces. The estimation of the malnutrition prevalence in 2020 also indicated a decrease in the prevalence of all indicators among children. Conclusions. Despite the decreasing trend of malnutrition over the past three decades, the prevalence of stunting, underweight and wasting is still high in food insecure provinces. Moreover, following COVID-19 pandemic and its economic consequences, increase of the prevalence of malnutrition especially in food insecure provinces is plausible.